An AN-GA controlled SEPIC converter for photovoltaic grid integration - Priyadarshi N.; Padmanaban S.; Holm-Nielsen J.B.; Ramachandaramurthy V.K.; Bhaskar M.S. (Institute of Electrical and Electronics Engineers Inc., 2023)
Mean square error; Neural networks; Photovoltaic cells; Power converters; Power electronics; Vector spaces; Voltage control; Bayesian regulation; Grid; Photovoltaic; Photovoltaic systems; Root mean square errors; SEPIC; Single ended primary inductor converter (SEPIC); Space vector pulse width modulation; Genetic algorithms